2007
DOI: 10.1145/1243418.1243429
|View full text |Cite
|
Sign up to set email alerts
|

A design for high-performance flash disks

Abstract: Most commodity flash disks exhibit very poor performance when presented with writes that are not sequentially ordered. We argue that performance can be significantly improved through the addition of sufficient RAM to hold data structures describing a fine-grain mapping between disk logical blocks and physical flash addresses. We present a design that accomplishes this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 1 publication
1
96
0
Order By: Relevance
“…LAST uses a block-level map-ping for most of the data and a page-level mapping for a small subset of the data [19]. Birrell et al [5] proposed a pagelevel mapping with a flat mapping table in RAM; this requires a large RAM in the SSD.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…LAST uses a block-level map-ping for most of the data and a page-level mapping for a small subset of the data [19]. Birrell et al [5] proposed a pagelevel mapping with a flat mapping table in RAM; this requires a large RAM in the SSD.…”
Section: Related Workmentioning
confidence: 99%
“…To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. shown that many of them perform poorly on random-write workloads [5,2]. Random read performance is often excellent, on par with sequential reads.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The migration process can take a relatively large amount of time, which explains the large response time for some request sizes. Other researcher [38] characterize the timing performance of Flash memory, and show a similar variation in performance.…”
Section: Resultsmentioning
confidence: 72%